Optimalisasi Rute Distribusi Produk CNG dengan Metode Saving Matrix dan Nearest Neighbor pada CV. XYZ - Dani Ade Bastian; Febrina Agusti; Ringgo Ismoyo Buwono (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Product distribution that does not optimally consider the distance traveled and vehicle capacity can increase the company's operational costs. This study aims to optimize distribution routes using the Saving Matrix and Nearest Neighbor methods and compare the efficiency level of the proposed routes with the company's actual routes. The results showed that the distribution routes were successfully optimized from 6 routes to 4 routes. The total distribution distance was reduced from 273 km to 196.03 km or experienced savings of 76.97 km (28.19%). Distribution costs decreased from Rp10,674,438 to Rp8,107,482 resulting in savings of 24.05%, while fleet capacity utilization increased from 54% to 80%. These results indicate that the combination of the Saving Matrix and Nearest Neighbor methods is effective in increasing the efficiency of CNG product distribution at CV. XYZ.